Assessing Usability of Learning Experience Prototype - Ramli, Ratna Zuarni; Sahari @ Ashaari, Noraidah; Mat Noor, Siti Fadzilah; Mat Noor, Mahanem; Abdul Majid, Nazatul Aini; Dahlan, Hadi Affendy; Abdul Wahab, Amelia Natasya (International Journal of Emerging Technologies in Learning (iJET), 2022)
The boost of mobile devices and internet technologies has led to the development of new content geared to enhance the learning experience of students while simultaneously ensuring the economizing of the teacher’s time. The era of industrial revolution 4.0 transformed many aspects of life including the basic approaches towards teaching and learning. The needs and demands of students and teachers are changing in line with the revolution of emerging technologies. However, even with the advent of technology, STEM subjects are yet to fully grasp the attention of students. Learning especially in secondary schools and higher education intuitions needs to be redesigned to improve students’ learning experience, especially in STEM subjects which involve complex concepts and processes that are difficult to visualize and require students to be fully engaged. Accordingly, this paper discusses the design and development of a learning experience model aimed at improving the teaching of Biology subjects. The model emphasized on three factors; content, pedagogy and interaction. Multimedia elements such as 2D graphic, video, AR with 3D object and gamification concepts were included in the design. A prototype called m-BioP was developed based on the designed model and heuristic evaluation was performed to ensure the application’s usability. It was verified by six experts and it is identified that 19/24 (79%) items are well designed and some changes (8/24 items) require improvement. Future studies need to be conducted to approved the designed model.